Patient factors associated with receiving reversal therapy in oral anticoagulant‐related intracerebral hemorrhage. (16th August 2022) - Apostolaki‐Hansson, Trine; Ullberg, Teresa; Norrving, Bo; Petersson, Jesper
Abstract : Background: We aimed to describe baseline characteristics of patients with oral anticoagulant‐related intracerebral hemorrhage (OAC‐ICH) in Sweden and to identify predictive variables associated with receiving hemostatic treatment in the event of OAC‐ICH. Methods: We performed an observational study based on data from Riksstroke and the Swedish Causes of Death Register to define baseline characteristics of patients with OAC‐ICH who received reversal treatment compared with patients who did not receive reversal treatment during 2017–2019. Predictive analysis was performed using multivariable logistic regression to identify odds ratios for factors associated with receiving OAC reversal treatment. Results: We included 1902 patients (( n  = 1146; OAC reversal treatment) ( n  = 756; no OAC reversal treatment)). The proportion of non‐Vitamin K oral anticoagulant associated ICH (NOAC‐ICH) patients who received reversal treatment was 48.4% and the proportion of Vitamin K antagonist‐associated ICH (VKA‐ICH) patients was 72.9%. Factors associated with a lower odds of receiving reversal treatment were increased age (OR = 0.98; 95% CI: 0.96–0.99), previous stroke (OR = 0.78; 95% CI: 0.62–0.98), comatose LOC (OR = 0.36;95%CI: 0.27–0.48; ref . = alert), pre‐stroke dependency (OR = 0.72; 95% CI: 0.58–0.91), and NOAC treatment (OR = 0.34; 95% CI: 0.28–0.42). Care at a university hospital was not associated with higher odds of receiving reversal treatment compared to treatment at a county hospital. Conclusion: Treatment with a reversal agent following OAC‐ICH was related to several patient factors including type of OAC drug. We identified that only 48% of patients with NOAC‐ICH received hemostatic treatment despite an increase in these cases. Further studies are required to guide the use of reversal therapies more precisely, particularly in NOAC‐ICH.